DIRECTIVE SPEECH ACTS IN MARIANNE NOVEL BY RISA SARASWATI PRAGMATIC STUDY - Dewi, Ni Putu Juliani Lestari; Anabokay, Yanrini; Ndun, Yandri Susuek; Isu, Rudolof Jibrael (English Education Department, 2022)
Speech acts are a person s ability to use language to convey messages or goals from speakers to speech partners Then this speech act is not only found in everyday conversations but can be found in other media such as novels Novel is a media for conveying messages and the purpose of writing and to provide entertainment to every reader Novel is a story or fiction that presents a deeper aspect of human life which is constantly changing and a meaningful dynamic unity One of the interesting novels and deserves to be studied is Marianne novel This novel was written by one great Indonesian writer named Risa Saraswati In this study the researcher conducted a directive speech act and used Marianne novel as a data source in this study This research is qualitative research using descriptive method The findings of this study there are as many as 12 utterances The forms of directive speech acts in this study include: 1 speech acts of requestives as many as 3 utterances 2 speech acts directive of questions just 1 utterance 3 speech acts directive of requirements as many as 2 utterances 4 prohibitive speech acts 2 utterances 5 permissive speech acts just 1 utterance and 6 advice directive speech around 3 utterances and each of these utterances has intentions and goals from the speaker to the speech partner < p>